Verification of Mythological Material on Celebrations as Recorded by Matthaeus Praetorius: the Celebration of Midsummer Herb Fest and Driving the Cattle out to Pasture - Vičinskas, Žydrūnas (Tautosakos darbai, 2018)
Authenticity of the mythological information by Matthaeus Praetorius (Matthäus Prätorius) regarding the sowing festival was already discussed in our previous publication. That was the first work in the intended series of articles seeking to verify the reliability of data on celebrations described by Praetorius (sowing, midsummer herb fest, driving the cattle out to pasture, rye-harvesting, grain harvesting Samborios / Sąbarios, driving the cattle back to stable, Gabjaugis, and taking manure out to fields). The introduction to this article presents general insights (characterizations) regarding various agricultural celebrations that Praetorius recorded, potentially reflecting or having preserved the relics of the ancient Baltic religious behavior. For this reason, it would be useful for the reader who wants to go deeper into the topic in question to get familiar with the aforementioned material. The main objective of this publication is verifying the reliability of the mythological information on celebrating midsummer herb fest and driving the cattle out to pasture recorded by Matthaeus Praetorius in his work “Deliciae Prussicae oder Preussische Schaubühne” (Deliciae Prussicae or Prussian Theater). We also review and assess the explications by the 20th–21st century scholars who analyzed the aforementioned data provided by Praetorius. An overview and analysis of the mythological information on celebrating midsummer herb fest and driving the cattle out to pasture as recorded by Matthaeus Praetorius shows that the 20th–21st century scholars split in two parts according to their use and assessment of his material. The first part did not discuss the authenticity of Praetorius’ mythological data on celebrating midsummer herb fest and / or driving the cattle out to pasture, considering the information to be quite reliable, and used it in their works (Pranė Dundulienė, Daiva Vaitkevičienė, Nijolė Laurinkienė, and Rimantas Balsys). The second part grasped the problem of the authenticity of the mythological information provided by Praetorius, but hesitated to engage in its verification (Jonas Balys, Kristina Blockytė). In summary, verification of the “Prussian Theater” revealed that the mythological material provided by Praetorius on celebrations of midsummer herb fest and driving the cattle out to pasture is rather authentic and reliable, since Matthaeus Praetorius’ mythological data in question in many cases mirrors much later ethnographic information.